Harnessing the Innate Effector: A Narrative Review of Advancing Strategies in CAR Engineering, Metabolic Reprogramming, and TME Resistance of Natural Killer Cells for Cancer Immunotherapy - Agustina, Rita; Lestari, Endah Agustina; Sidiq, Husni Ahmad; Nazar, M. Ariq (International Journal of Cell and Biomedical Science, 2025)
Natural Killer (NK) cell-based immunotherapy is rapidly emerging as a promising modality for cancer treatment. As pivotal players in the innate immune system, cells independently recognize and eliminate malignant cells without prior sensitization, offering distinct advantages over other cell-based therapies. This review highlights the current landscapes of NK cell adoptive therapy, from fundamental biology to cutting-edge clinical applications. It highlights how advancing NK cell sources, including peripheral blood, umbilical cord blood, established cell lines, and the increasingly significant induced pluripotent stem cells (iPSCs), are driving wider, more standardized therapeutic use. The multifaceted strategies employed to enhance NK cell efficacy are being explored, including advanced expansion protocols and sophisticated genetic engineering techniques such as the introduction of Chimeric Antigen Receptors (CARs) and modifications to bolster antibody-dependent cellular cytotoxicity. Additionally, it also addresses the significant hurdles that remain, primarily the immunosuppressive tumor microenvironment (TME), and discusses innovative strategies being developed to overcome these challenges. By synthesizing preclinical data and results from the latest clinical trials, this review highlights the remarkable progress and bright future of NK cell therapy as a safer, effective, and more accessible cornerstone of cancer treatment.